2017
DOI: 10.1093/europace/eux030
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis associated with redo cardiac resynchronization therapy following complete device and lead extraction due to device-related infection

Abstract: Redo CRT implantation after device extraction owing to device-related infection has a low success rate and shows a higher rate of re-infection than that observed in patients who undergo CRT implantation for the first time. Further, patients whose blood cultures are positive for S. aureus show a particularly poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…The present study set out to investigate the usefulness of preoperative transesophageal echocardiography in the assessment of the long-term survival after TLE. The results are consistent with those observed in earlier studies [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] which showed that patient-dependent variables (demographic, related to the underlying disease, comorbidities, systemic infection) were the main risk factors for death at long-term follow-up. CIED-related factors, including the number of leads, left ventricular lead and ICD lead play a significant role, but secondary to the underlying condition [ 5 , 6 , 11 , 12 , 13 , 14 , 15 , 19 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study set out to investigate the usefulness of preoperative transesophageal echocardiography in the assessment of the long-term survival after TLE. The results are consistent with those observed in earlier studies [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] which showed that patient-dependent variables (demographic, related to the underlying disease, comorbidities, systemic infection) were the main risk factors for death at long-term follow-up. CIED-related factors, including the number of leads, left ventricular lead and ICD lead play a significant role, but secondary to the underlying condition [ 5 , 6 , 11 , 12 , 13 , 14 , 15 , 19 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Vegetations and LRIE have always been (in all previous analyses, including ours) one of the most potent factors decreasing chances of long-term survival [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Unfortunately, despite the improving standards [ 2 , 3 , 4 ] long-term mortality among patients after TLE performed due to LRIE does not improve as desired.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Verschlossene Zugangswege der Vv. subclaviae, der V. cava superior oder einer geeigneten CS-Vene sind häufig Gründe dafür [29][30][31]. Alternative CRT-Verfahren, unabhängig von den klassischen Zugangswegen, sind in diesen Szenarien immer attraktiv.…”
Section: Langzeitkomplikationen Und Reimplantationunclassified